2017
DOI: 10.1155/2017/7565870
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenitally Corrected Transposition of Great Arteries: An Infrequent Happenstance

Abstract: Congenitally corrected transposition of the great arteries (CCTGA) is rare form of congenital heart diseases. It may be present with or without associated anomalies. Patients with CCTGA are usually diagnosed at early stages of life due to associated anomalies, but they may even remain asymptomatic till later decades of their life. We report a case of a 42-year-old man who presented at neurosurgery department with dizziness, seizures, and loss of consciousness, in whom isolated CCTGA was discovered incidentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…And was managed with dual chamber implantable cardioverter defibrillator, 4 Similarly, Tandon et al also reported an incidental diagnosis of dextroversion CCTGA in a patient who presented with cocaine-induced acute myocardial infarction, 1 One more case report in which patient presented at neurosurgery department with dizziness, seizures, and loss of consciousness, in whom isolated CCTGA with third degree AV block was detected and was successfully managed with VVI mode permanent pacemaker implantation. 6 The symptoms commonly associated with occurrence of TR in CCTGA are decreased stamina, dyspnoea, chest pain, and palpitations. In about 20 to 50% of CCTGA patients, TR occurs in varying degree causing substantial morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And was managed with dual chamber implantable cardioverter defibrillator, 4 Similarly, Tandon et al also reported an incidental diagnosis of dextroversion CCTGA in a patient who presented with cocaine-induced acute myocardial infarction, 1 One more case report in which patient presented at neurosurgery department with dizziness, seizures, and loss of consciousness, in whom isolated CCTGA with third degree AV block was detected and was successfully managed with VVI mode permanent pacemaker implantation. 6 The symptoms commonly associated with occurrence of TR in CCTGA are decreased stamina, dyspnoea, chest pain, and palpitations. In about 20 to 50% of CCTGA patients, TR occurs in varying degree causing substantial morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…5 If asymptomatic, they have normal life expectancy. 6 We describe the anaesthetic management of a patient with CCTGA complicated with severe pulmonary stenosis and VSD who presented with trauma to both the upper limbs for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the suitable surgical procedure for most of TGA cases in children with VSD is an arterial switch operation [11]. There have been multiple case reports on patients of older age who are asymptomatic and hence undiagnosed until the fourth and fifth decades of life [12-13]. However, this study presents the case of a young 14-year-old female showing progressive SOB due to multiple complex cardiac defects from a developing country like Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple case reports of CCTGA being diagnosed in patients of older age [ 12 - 14 ]. Till date, the oldest reported patient with CCTGA is a 92-year-old woman from France [ 14 ].…”
Section: Discussionmentioning
confidence: 99%